2009
DOI: 10.1038/cdd.2008.190
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptors CXCR4 and CCR7 promote metastasis by preventing anoikis in cancer cells

Abstract: Chemokine receptors are essential mediators of the metastatic spread in various cancer types; however their precise function in the development of secondary tumors remains poorly understood. We report here a novel property of the chemokine receptors CXCR4 and CCR7 in inhibiting detachment-induced cell death -anoikis, which is believed to be one of the major blocks in the metastatic spread of various neoplasms. Activation of these chemokine receptors by their respective ligands, CXCL12 and CCL21 specifically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 40 publications
1
71
0
1
Order By: Relevance
“…MDA-MB-231 cells are known to express CCR7 (23,24) and migrate toward increasing concentration of CCL21 when cultured in 2D and exposed to a CCL21 gradient (25). The system consists of two channels separated by a region containing single cells suspended in a collagen I gel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MDA-MB-231 cells are known to express CCR7 (23,24) and migrate toward increasing concentration of CCL21 when cultured in 2D and exposed to a CCL21 gradient (25). The system consists of two channels separated by a region containing single cells suspended in a collagen I gel (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cooperation of CXCR4 and CCR7 in close association with their respective ligands have been reported to be responsible for anoikis, meaning reduced sensitivity to apoptosis normally caused by detachment of neoplastic cells from cellcell and cell-matrix contacts (29). This may implicate enhanced survival of mobile cancer cells in circulating blood or extracellular matrix.…”
Section: Ccr7mentioning
confidence: 99%
“…Our findings are consistent with previously reported data. Formation of cancer cell aggregates has been reported in hepatoma, breast, prostate, and lung cancer cell lines growing in suspension (Berezovskaya et al 2005, Zhang et al 2008, Kochetkova et al 2009). It has also been reported that formation of multi-cellular aggregates in non-adherent conditions is associated with overexpression of adhesion molecules (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 97%